The functions of punning utterances in English and Chinese: a cross-cultural perspective - Agnieszka Solska (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
Capitalizing on the universal linguistic feature of ambiguity, punning utterances can be found in languages as distinct as the Indo-European, marginally inflected English and the Sino-Tibetan, monosyllabic, inflectionless Chinese. Though forming a tiny fraction of the utterances produced in these languages, they tend to stand out and can be encountered in diverse communicative settings, including poetry and prose, jokes and comedy routines, advertising slogans and book titles. Whether perceived as “the lowest form of wit” or a lofty rhetorical device, they perform a wide range of functions which are often grounded in distinct cultural and historical backgrounds they are embedded in. The objective of this article is to identify the most striking differences in the functions served by typical English and Chinese puns and to investigate the cultural factors underlying these differences. Adopting Jakobson’s model of language functions as the organizing principle for the discussion, I examine a range of puns in the two languages, comparing and contrasting the motivations for their use.